Quantitating membrane bleb stiffness using AFM force spectroscopy and an optical sideview setup1. Issue 3 (9th March 2015) - Gonnermann, Carina; Huang, Chaolie; Becker, Sarah F.; Stamov, Dimitar R.; Wedlich, Doris; Kashef, Jubin; Franz, Clemens M.
<x xml:space="preserve">Abstract</x> Atomic force microscopy micro-indentation measurements in combination with an optical sideview setup to characterize the stiffness of blebbing and non-blebbing membranes in the same cell.